What Academic Library Leadership Lacks: Leadership Skills Directors Are Least Likely to Develop, and Which Positions Offer Development Opportunity - Harris, Colleen S. (The Journal of academic librarianship, 2016)
Though research into academic library director leadership has established a list of leadership skills required for success, little research has been done to establish which skills are more difficult to acquire than others, and which library positions best help aspiring library directors to acquire those skills. This research surveyed academic library directors at American Master's granting institutions about leadership skill development in their previous academic library positions. In particular, the leadership skills academic library directors indicated they had least opportunity to develop included fundraising and donor relations, school safety issues, legal issues, compliance issues, and facilities planning. For these leadership skills, data indicate that development opportunities are perceived to be limited to the academic library positions of director, assistant director, and positions where one is the head of multiple academic library departments.